Atomic-scale visualisation of fermion-pair condensates in strongly correlated quantum materials - Ren, W (2024)
Since its discovery in 1986, high-temperature superconductivity in copper oxides has puzzled researchers. Its intricate phase diagram, which unveils unusual physical properties, is particularly challenging to understand because of its strongly correlated nature. Despite numerous efforts, a consensus on the mechanism that forms electron-pair condensate underpinning the high-temperature superconductivity remains elusive. The research presented in this thesis endeavours to shed new light on the electron-pairing mechanism.